Synthesis of [2,2′-Bipyridine]-1,1′-diium Tricyanomethanide as a Bifunctional Nanostructured Ionic Liquid: Application to the Synthesis of 2-Aryl-5-methyl-2,3-dihydro-1H-3-pyrazolone Derivatives - Zolfigol, Mohammad Ali; Mansouri, Navid; Baghery, Saeed (Synlett, 2016)
{[2,2′-BPyH][C(CN)3]2} was synthesized and fully characterized by IR, 1H NMR, 13C NMR, mass, X-ray diffraction patterns (XRD), scanning electron microscopy (SEM), transmission electron microscopy (TEM), thermogravimetric (TG), and differential thermal (DTA) analysis. [2,2′-Bipyridine]-1,1′-diium tricyanomethanide {[2,2′-BPyH][C(CN)3]2} as a bifunctional nanostructure ionic liquid beneficial catalyzed the synthesis of 2-aryl-5-methyl-2,3-dihydro-1H-3-pyrazolone derivatives via the one-pot, four-component condensation reaction of aromatic aldehydes, ethyl acetoacetate, phenyl hydrazine, and β-naphthol under solvent-free conditions at room temperature. The major advantages of the offered process are efficient catalysis and recyclability of catalyst.
Keywords: nanostructure ionic liquid; [2,2′-bipyridine]-1,1′-diium tricyanomethanide; 2-aryl-5-methyl-2,3-dihydro-1H-3-pyrazolone; solvent-free condition